IMPLEMENTASI EDUPRENEURSHIP DI SMP NEGERI 1 KABILA DALAM MATA PELAJARAN P5 - Sri Intan Meilan Igirisa; Imam Mashudi (Akademika : Jurnal Ilmiah Media Publikasi Ilmu Pengetahuan dan Teknologi, 2025)
This research examines edupreneurship implementation through Projek Penguatan Profil Pelajar Pancasila (P5) at SMP Negeri 1 Kabila, focusing on regulatory frameworks, project-based practices, encountered challenges, overcoming strategies, and development recommendations. The study aims to reveal P5 effectiveness in fostering entrepreneurial spirit among junior high students via authentic business simulations like fruit ice production using school vouchers. Qualitative descriptive method utilized in-depth interviews, supported by school documents and project observations; data analyzed thematically with source triangulation. Findings indicate P5 regulations effectively integrate Job Based Learning (JBL) where students manage group budgets, produce and market fruit ice via non-cash vouchers, building comprehensive entrepreneurial skills across business, education, social, and governance domains. Primary challenges include time constraints from concurrent projects, limited sales booth facilities, and low student motivation impacting participation and creativity, addressed through parent-committee collaboration and practical innovations. Recommendations encompass cross-subject integration (Mathematics for profit-loss, Indonesian for proposals), periodic bazaars, digital promotion via Canva/Instagram, and process-focused evaluations emphasizing creativity over outcomes. In conclusion, localized P5 edupreneurship demonstrates high potential when supported by holistic ecosystems, offering practical insights for Kurikulum Merdeka optimization at SMP level.